Regulation of Dendritic Cell Functions against Harmful Respiratory Pathogens by a Cysteinyl Leukotrienes Receptor Antagonist - Hiroto Matsuse M.D., Ph.D.; Hiroko Hirose M.D., Ph.D.; Susumu Fukahori M.D., Ph.D.; Tomoko Tsuchida M.D., Ph.D.; Shinya Tomari M.D., Ph.D.; Tetsuya Kawano M.D., Ph.D.; Chizu Fukushima M.D., Ph.D.; Shigeru Kohno M.D., Ph.D. (Allergy & Rhinology, 2012)
Cysteinyl leukotriene receptor antagonist (LTRA) is a widely used medicine for asthma. Cysteinyl leukotrienes (cysLTs) are involved in the regulation of dendritic cell (DC) function. However, the effects of LTRA on DC-related antimicrobial immunity against harmful respiratory pathogens remain unknown. The purpose of this study was to examine the effects of LTRA administered in vivo on DC function against representative respiratory pathogens in vitro. Pulmonary DCs were isolated from four groups of mice: control, mite allergen sensitized (AS), and AS mice treated with the corticosteroid dexamethasone (Dex) or with the LTRA pranlukast (Prl). These DCs were incubated with mite allergen, lipopolysaccharide (LPS), Aspergillus fumigatus, or respiratory syncytial virus (RSV). IL-10 and IL-12 production was then determined. Dex treatment significantly inhibited lipopolysaccharide (LPS)-induced IL-10 and IL-12 production as well as baseline IL-12 production in AS mice. The Prl did not significantly inhibit LPS-induced IL-10 and IL-12 production in AS mice. More importantly, Prl significantly increased IL-10 and IL-12 in AS mice after RSV infection. This study shows that LTRA that is used for asthma potentially up-regulates antimicrobial immunity through modulation of DC function against some respiratory infections without immunosuppression.